2019
DOI: 10.4082/kjfm.18.0139
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Obesity Phenotypes and Early Renal Function Decline in Adults without Hypertension, Dyslipidemia, and Diabetes

Abstract: Background: The prevalence of chronic kidney disease is increasing worldwide. Several studies have suggested that obesity is associated with early renal dysfunction. However, little is known about the relationship between obesity phenotypes and early renal function decline. Therefore, this study aimed to identify the relationship between obesity phenotypes and early renal function decline in adults without hypertension, dyslipidemia, and diabetes. Methods: We conducted a cross-sectional analysis of clinical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…Meanwhile, in 135 of first-degree relatives, higher frequency of obesity was noted, followed by overweight and normal weight. Several previous studies have reported similar findings, that increased BMI was independent risk factor for CKDs in general population, diabetes and hypertension (25,26,27,28,29). Indeed, obesity is known to affect hemodynamic, insulin resistance, adipokines changes, low grade inflammation, oxidative stress and endothelial dysfunction, therefore has been suggested to be a risk factor of CKDs.…”
Section: Discussionsupporting
confidence: 54%
“…Meanwhile, in 135 of first-degree relatives, higher frequency of obesity was noted, followed by overweight and normal weight. Several previous studies have reported similar findings, that increased BMI was independent risk factor for CKDs in general population, diabetes and hypertension (25,26,27,28,29). Indeed, obesity is known to affect hemodynamic, insulin resistance, adipokines changes, low grade inflammation, oxidative stress and endothelial dysfunction, therefore has been suggested to be a risk factor of CKDs.…”
Section: Discussionsupporting
confidence: 54%
“…In the only meta-analysis on MetS in AUD patients none of the five studies analyzed the role of kidney disease in the syndrome 13 . Besides, some other studies in different populations at risk of MetS included the alcohol consumption as a covariate but they did not analyze the association of eGFR and MetS 28 30 .…”
Section: Discussionmentioning
confidence: 99%
“…One can observe increase renal sodium reabsorption, besides the recruitment of functional reserve with glomerular hyper ltration. Obesity can also promote hypo ltration, increasing the risk for CKD [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%